Positive Collaboration in Rehabilitation Nursing Enhances Fall Efficacy and Confidence in Elderly Patients with Cerebral Infarction - Luo F; Xu W; Xu Y; Lou L; Xu C (Therapeutics and Clinical Risk Management, 2025)
Fang Luo,1 Wenyao Xu,2 Yaqin Xu,3 Lingdi Lou,1 Chunyan Xu3 1Department of Rehabilitation Medicine - Cerebrovascular Accident Rehabilitation Ward, Zhejiang Provincial People’s Hospital, Hangzhou, Zhejiang, 310024, People’s Republic of China; 2Convalescence Zone 1, Air Force Hangzhou Special Service Convalescence Center, Hangzhou, Zhejiang Province, 310007, People’s Republic of China; 3Department 5 of Geriatrics, Zhejiang Provincial People’s Hospital, Hangzhou, Zhejiang, 310007, People’s Republic of ChinaCorrespondence: Chunyan Xu, Email xbw127@126.comBackground: Cerebral infarction is a prevalent disabling condition among the elderly, often leading to limb dysfunction and psychological challenges that significantly impair quality of life. Traditional nursing approaches have primarily focused on physical rehabilitation; however, growing evidence highlights the importance of psychological factors—such as emotional well-being and rehabilitation confidence—in influencing recovery outcomes. Positive collaboration in rehabilitation nursing, which involves coordinated efforts among patients, healthcare providers, and family members, has emerged as a holistic approach to enhance both physical and psychological recovery.Objective: To analyze the effects of positive collaboration concept rehabilitation nursing on elderly patients with cerebral infarction, focusing on fall efficacy and rehabilitation confidence.Methods: A retrospective analysis was conducted on clinical data from 106 elderly patients with cerebral infarction, admitted from October 2022 to April 2024. Patients were divided into a control group (n=53, receiving routine care) and an observation group (n=53, receiving positive collaboration rehabilitation nursing). Neurological function (NIHSS), negative emotions (SAS, SDS), fall efficacy (MFES), activities of daily living (ADL), quality of life (SS-QOL), rehabilitation confidence (CaSM), and nursing satisfaction (NSNS) were compared between the two groups.Results: The observation group showed significantly lower NIHSS scores at 2 weeks and 1 month post-intervention (P< 0.05). Both groups demonstrated reduced SAS and SDS scores, with the observation group showing greater improvement (P< 0.05). A higher proportion of patients in the observation group (56.60%) showed excellent fall efficacy compared to the control group (37.74%) (P< 0.05). The observation group also had greater improvements in ADL, SS-QOL, and rehabilitation confidence, with higher patient satisfaction (90.57% vs 71.70%, P< 0.05).Conclusion: Positive collaboration rehabilitation nursing significantly improves neurological function, emotional well-being, fall efficacy, and quality of life in elderly patients with cerebral infarction. This approach increases patient and family satisfaction, highlighting the potential benefits of integrating collaborative care into clinical practice.Keywords: cerebral infarction, elderly, positive collaboration concept rehabilitation nursing, fall efficacy, rehabilitation confidence, satisfaction, effect, impact